PENGARUH PENERAPAN MANAJEMEN KELAS TERHADAP MOTIVASI BELAJAR SISWA - Sumita, Isma; Berliani, Teti (Equity In Education Journal, 2024)
This study aims to determine the effect of the application of classroom management on the learning motivation of class VIII students at SMP Negeri 1 Kapuas Barat Kapuas Regency. The research method used was a quantitative approach, with the research subject being class VIII students of SMP Negeri 1 Kapuas Barat Kapuas Regency in the 2023⁄2024 academic year totaling 76 students. The data in the study were collected using a questionnaire technique, then analyzed using a simple linear regression formula. The results showed that the simple linear regression equation of Y = a + bX was Y = 16.693 + 0.700X. The constant value (a) is 16.693. Based on the results of hypothesis testing, t count 8.329> t table 1.992 was obtained, so that the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. This shows that the classroom management variable has a significant effect on student learning motivation at State Junior High School 1 Kapuas Barat Kapuas Regency by 48.4% and the rest is influenced by other variables not examined.